Linear Epitope Binding Patterns of Grass Pollen-Specific Antibodies in Allergy and in Response to Allergen-Specific Immunotherapy - Thörnqvist, Linnea; Sjöberg, Ronald; Greiff, Lennart; van Hage, Marianne; Ohlin, Mats (Frontiers in Allergy, 2022)
Allergic diseases affect many individuals world-wide and are dependent on the interaction between allergens and antibodies of the IgE isotype. Allergen-specific immunotherapy (AIT) can alter the development of the disease, e.g., through induction of allergen-specific IgG that block allergen-IgE interactions. The knowledge of epitopes recognized by allergy-causing and protective antibodies are limited. Therefore, we developed an allergome-wide peptide microarray, aiming to track linear epitope binding patterns in allergic diseases and during AIT. Here, we focused on immune responses to grass pollen allergens and found that such epitopes were commonly recognized before initiation of AIT and that AIT commonly resulted in increased antibody production against additional epitopes already after 1 year of treatment. The linear epitope binding patterns were highly individual, both for subjects subjected to and for individuals not subjected to AIT. Still, antibodies against some linear epitopes were commonly developed during AIT. For example, the two rigid domains found in grass pollen group 5 allergens have previously been associated to a diversity of discontinuous epitopes. Here, we present evidence that also the flexible linker, connecting these domains, contains regions of linear epitopes against which antibodies are developed during AIT. We also describe some commonly recognized linear epitopes on Phl p 2 and suggest how antibodies against these epitopes may contribute to or prevent allergy in relation to a well-defined stereotyped/public IgE response against the same allergen. Finally, we identify epitopes that induce cross-reactive antibodies, but also antibodies that exclusively bind one of two highly similar variants of a linear epitope. Our findings highlight the complexity of antibody recognition of linear epitopes, with respect to both the studied individuals and the examined allergens. We expect that many of the findings in this study can be generalized also to discontinuous epitopes and that allergen peptide microarrays provide an important tool for enhancing the understanding of allergen-specific antibodies in allergic disease and during AIT.